2022
DOI: 10.1126/scisignal.abj0644
|View full text |Cite
|
Sign up to set email alerts
|

Redox-dependent internalization of the purinergic P2Y 6 receptor limits colitis progression

Abstract: Cysteine modification of the purinergic receptor P2Y 6 R promotes internalization and degradation and limits colitis progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Endothelial-dependent vasorelaxation, induced by UDP stimulation, and contraction, induced by UDP upon the inhibition of endothelial nitric oxide synthase, were abolished in P2Y 6 R-deficient aortas [ 21 ]. P2Y 6 R KO mice did not display atherosclerosis, vascular inflammation, age-related hypertension and intestinal inflammation [ 14 , 15 , 22 ]. Compared to wild-type mice, P2Y 6 R KO mice show a significant resistance to the skin papilloma-inducing effects of 7,12-dimethylbenz[a]anthracene/12-O-tetradecanoylphorbol-13-acetate [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endothelial-dependent vasorelaxation, induced by UDP stimulation, and contraction, induced by UDP upon the inhibition of endothelial nitric oxide synthase, were abolished in P2Y 6 R-deficient aortas [ 21 ]. P2Y 6 R KO mice did not display atherosclerosis, vascular inflammation, age-related hypertension and intestinal inflammation [ 14 , 15 , 22 ]. Compared to wild-type mice, P2Y 6 R KO mice show a significant resistance to the skin papilloma-inducing effects of 7,12-dimethylbenz[a]anthracene/12-O-tetradecanoylphorbol-13-acetate [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, cardiomyocyte-specific overexpression of P2Y 6 R exacerbates pressure overload-induced heart failure [ 13 ]. We also reported that P2Y 6 R contributes to the progression of age-related hypertension and inflammatory bowel disease, and P2Y 6 R knockout mice show the prevention of tissue remodeling, including fibrosis and inflammation [ 14 , 15 ]. These results suggest a positive relationship between P2Y 6 R expression and the severity of tissue fibrosis and inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown how cells recognize 6-MSITC. However, sulforaphane, an isothiocyanate, has recently been reported to bind to P2Y6 receptors [ 16 ], and it is possible that 6-MSITC may bind to cells by the same mechanism. We think further studies are needed to prove the hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Reactions were prepared following the manufacturer’s protocol. For BMDMs, total RNA was extracted and cDNA was synthesized as previously described [ 64 ]. Quantitative real-time PCR was performed as previously described [ 64 ].…”
Section: Methodsmentioning
confidence: 99%
“…For BMDMs, total RNA was extracted and cDNA was synthesized as previously described [ 64 ]. Quantitative real-time PCR was performed as previously described [ 64 ]. Primer sequences used are summarized in Table S1 .…”
Section: Methodsmentioning
confidence: 99%